PENDAMPINGAN METODE PEMBELAJARAN JARAK JAUH (PPJ) DI ERA NEW NORMAL PADA SISWA TAMAN BACA MASYARAKAT (TBM) CARITA - Muhammad Hapizd Kamaludin; Teuku Raehan Revikhasyah; Alwansyah Rifa’i; Fikri Sabillah; Tukfatul Anam; Nizar Alwan (Lembaran Masyarakat: Jurnal Pengembangan Masyarakat Islam, 2020)
The closure of all teaching and learning activities at educational institutions throughout Indonesia starting March 2020, to assist in efforts to contain the spread of the Covid-19 outbreak. This paper aims to analyze learning assistance in the era of distance learning. This study used qualitative and participatory learning and action methods. This study showed that students have impacedt of teaching and learning activities which is conducted by online at their respective homes, many problems began to arise from mounting homework, incomprehensible assignments, psychologically shaken children because they were not put up with online learning, and parents who are busy working to buy their children online learning needs. Therefore, the opening of several community reading parks or Taman Baca Masyarakat (TBM) for short, if it can help a little bit the burden of parents and the burden of the students themselves, in doing the tasks given by the Educational Institution, with face-to-face offline learning methods.